EFEKTIVITAS DAN EFISIENSI PENGGUNAAN MIKROPIPET DALAM PENERAPAN INSEMINASI BUATAN TERHADAP FERTILITAS TELUR AYAM LOKAL: EFFECTIVENESS AND EFFICIENCY OF USING MICROPIPETTES IN THE APPLICATION OF ARTIFICIAL INSEMINATION ON LOCAL CHICKEN EGG FERTILITY - Sudrajat, Mashudy; Handarini, Ristika; Zandos, F; Rahmi, Annisa; Baharun, Abdullah (Universitas Djuanda, 2023)
The high demand for local chicken products in large quantities cannot be met by local chicken farmers. The high demand for local chicken products requires alternatives to increase productivity, one of which is using Artificial Insemination (AI) technology. This research aims to evaluate effectiveness and efficiency the use of micropipette in implementing artificial insemination to egg weight, fertility and hatchability of local chicken. 108 local chicken hen from three local chicken strain i.e. KUB, Merawang and IPB D-1 (each of strain 36 chicken) were used in this research and were subjected to artificial insemination using micropipette. The semen collection is done using the massase method which involves two local male chickens each (KUB, Merawang, and IPB D-1). The research was conducted using a two factors factorial complete randomized design, the factors were local chicken strain (KUB, Merawang, and IPB D-1) and amount of fresh semen (5,10, and 15 microliter), each treatment were repeated four times and each experimental unit consisted of three chickens. The results were obtained from the research were egg weight ranged between 46,15±0,40-46,95±0,48 gram with average 46,56±0,14 gram, egg Fertility ranged from 80,18±0,21%-86,11±3,21% with average 83,14± 2,3% and egg hatchability ranged from 91,03±2,84-94,45±6,41% with mean of 92,96±2,16%%. There were no significant effect either from local chicken strain nor amount of fresh semen on all variables. In Addition, there was no interaction between two factors.